2011
DOI: 10.1007/s00115-011-3310-y
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermie unter Olanzapin

Abstract: A review of the current literature reveals that thermoregulatory disturbances as sequelae of antipsychotic drug administration depend on individual disposition as well as various independent risk factors such as environmental temperature, somatic comorbidities, endocrinological abnormalities (e.g. hypothyroidism) and structural damage of the brain. A complex interaction of dopaminergic regulatory mechanisms in the ventral hypothalamus and peripheral vaso- and sudomotor adjustments seems to be causative. Hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…The increased energy storage induced by olanzapine was extensively considered a result of both increased energy intake (such as hyperphagia) [43], [44] and reduced energy expenditure (such as decreased thermogenesis) [45], [46]. Our results showed that olanzapine treatment increased food intake by 21.2%, enhanced fat accumulation by 52.1%, and reduced brown fat amount by 39.3%, when compared with the control group.…”
Section: Discussionmentioning
confidence: 50%
“…The increased energy storage induced by olanzapine was extensively considered a result of both increased energy intake (such as hyperphagia) [43], [44] and reduced energy expenditure (such as decreased thermogenesis) [45], [46]. Our results showed that olanzapine treatment increased food intake by 21.2%, enhanced fat accumulation by 52.1%, and reduced brown fat amount by 39.3%, when compared with the control group.…”
Section: Discussionmentioning
confidence: 50%
“…This is the twelfth reported patient with olanzapine-induced hypothermia and the youngest pediatric patient with olanzapine-induced hypothermia described in the literature (PubMed Search for olanzapine and hypothermia 13.09.2011) (see Table 1) [5][6][7][8][9][12][13][14][15][16]. According to the literature, the risk of hypothermia is highest following initiation of the drug or after an increase in dosage.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Metabolism of olanzapine is via CYP 1A2 pathways, with no relevant genetic polymorphisms currently on record [7,8]. It is known that in normal humans there is a balance between the down-regulation of the body temperature by dopamine and the up-regulation of the body temperature by serotonin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De plus, une revue de la base nationale de pharmacovigilance française menée en 2013, identifie les antipsychotiques comme les psychotropes les plus pourvoyeurs d'hypothermie (3). Dans notre cas, nous retrouvons plusieurs facteurs de risque d'hypothermie induite par les antipsychotiques identifiés dans la littérature : l'utilisation conjointe d'une benzodiazépine (2,4), qui altère la thermorégulation par le bais de la transmission GABAergique (5), l'hospitalisation en chambre de soins intensifs, nécessitant un habillement sommaire (1) et la présence d'air conditionné (2), le choix de la Rispéridone, antipsychotique le plus fréquemment incriminé dans les cas d'hypothermie (1), et enfin l'association de plusieurs antipsychotiques (6). En effet, la cinétique de l'épisode plaide pour une action additive des différents antipsychotiques, sans qu'une molécule ne puisse être incriminée à elle seule.…”
Section: Discussionunclassified